Cerebellar contribution to context processing in extinction learning and recall - Chang, Dae-In; Lissek, S.; Ernst, T. M.; Thürling, M.; Uengoer, M.; Tegenthoff, M.; Ladd, Mark E.; Timmann, D. (The cerebellum, 2015)
Whereas acquisition of new associations is considered largely independent of the context, context dependency is a hallmark of extinction of the learned associations. The hippocampus and the prefrontal cortex are known to be involved in context processing during extinction learning and recall. Although the cerebellum has known functional and anatomic connections to the hippocampus and the prefrontal cortex, cerebellar contributions to context processing of extinction have rarely been studied. In the present study, we reanalyzed functional brain imaging data (fMRI) of previous work investigating context effects during extinction in a cognitive associative learning paradigm in 28 young and healthy subjects (Lissek et al. Neuroimage. 81:131-3, 2013). In that study, event-related fMRI analysis did not include the cerebellum. The 3 T fMRI dataset was reanalyzed using a spatial normalization method optimized for the cerebellum. Data of seven participants had to be excluded because the cerebellum had not been scanned in full. Cerebellar activation related to context change during extinction learning was most prominent in lobule Crus II bilaterally (p < 0.01, t > 2.53; partially corrected by predetermined cluster size). No significant cerebellar activations were observed related to context change during extinction retrieval. The posterolateral cerebellum appears to contribute to context-related processes during extinction learning, but not (or less) during extinction retrieval. The cerebellum may support context learning during extinction via its connections to the hippocampus. Alternatively, the cerebellum may support the shifting of attention to the context via its known connections to the dorsolateral prefrontal cortex. Because the ventromedial prefrontal cortex (vmPFC) is critically involved in context-related processes during extinction retrieval, and there are no known connections between the cerebellum and the vmPFC, the cerebellum may be less important during extinction recall.
Gesehen am 13.11.2020